THE EFFECT OF PRODUCT QUALITY, PROMOTION, PRICE ON FORE COFFEE PURCHASE DECISION IN MEDAN CITY - WIlly Surya Halim; Lidya Natalia Pasaribu; Emmelly Emmelly (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
The study is based on the growing public interest in coffee shops, especially among young people. The variables used in this study are product quality (X1), promotion (X2), price (X3), and purchasing decisions (Y). The purpose of this study is to determine how product quality, marketing, and price influence the decisions made by Fore Coffee customers in Medan City about what they buy. Ini adalah studi associative quantitative yang melibatkan pelanggan Fore Coffee di Kota Medan. A sample dari 100 responden dipilih secara random. Software Partial Least Squares (PLS) dan SmartPLS digunakan untuk menganalisis data. The findings demonstrated that pricing (X3) had a positive and significant impact on purchasing decisions (Y), promotion (X2) had no positive and significant impact on purchasing decisions (Y), and product quality (X1) had a positive and significant impact on purchasing decisions (Y). Customers' decisions to buy Fore Coffee were largely influenced by price, product quality, and promotion (R-square value of 87.6%). According to this data, the primary elements influencing consumers' decisions to buy a product are its quality and price; present promotions are insufficient to substantially alter consumers' choices.